Clinical features of genetic cutaneous porphyrias in Israel: A nationwide survey. Issue 3 (20th December 2020) - Snast, Igor; Kaftory, Ran; Lapidoth, Moshe; Mamet, Rivka; Hodak, Emmilia; Edel, Yonatan; Levi, Assi
Abstract: Background: There are three major types of genetic cutaneous porphyrias (GCP): erythropoietic protoporphyria (EPP), variegate porphyria (VP), and hereditary coproporphyria (HCP). Scarce data are available regarding their impact on patients' quality of life in the Mediterranean region. Purpose: To describe the cutaneous features of GCP in Israel. Methods: An established nationwide cohort of patients with GCP diagnosed during 1988‐2019 was surveyed by telephone for cutaneous features of GCP. Impact on quality of life was assessed using the Dermatology Life Quality Index . Results: Of the 95 patients with GCP, 71 (75%) completed the survey (21 HCP; 40 VP; 10 EPP). All EPP patients reported cutaneous symptoms compared with 58% of VP and 5% of HCP ( P < .001). Mean age at symptom onset was 7 ± 6 years in EPP and 25 ± 15 years in VP ( P < .001). Photosensitivity was the most common symptom in EPP (90%). In VP photosensitivity (52%), blistering (52%) and scarring (74%) were all common symptoms. In both VP and EPP, the dorsal hands/forearms were the most affected regions (≥96%), and in ≥ 78%, symptoms occurred on an almost daily basis. All EPP patients changed their lifestyle due to cutaneous symptoms vs 57% in VP. Major effect on quality of life was observed among EPP patients compared with a moderate effect in VP. No treatment was effective in EPP, while phototherapy and moisturizers were effective in 5 of 7 (71%) VP patients. Conclusion: This study sheds light on the cutaneous features of the GCP, which have a substantial effect on patients' quality of life.